(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
This article presents statistical analyzes on the rational use of energy in food production and processing. Today, analysis data on energy consumption in the whole world and in Uzbekistan, depending on the growth of the population and, accordingly, the increase in the demand for food products, are presented. Also, the minimum consumption norms and consumption indicators of food products are given in Uzbekistan by year.